Transformative Islam and Peasant Independence: Experiences from an Indonesian Village - Fanani, Muhyar; Abdullah, Irwan; Hasyim, Nur; Supriadi, Endang (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Indonesian peasants have been dependent on market forces and global phenomena since the establishment of the New Order (1966), and this has been detrimental to their welfare. However, this phenomenon has long been ignored by scholars, and thus the government has received little feedback regarding the creation of fairness and justice in agricultural management. This study, thus, seeks to empower farmers by transforming their traditional understanding of Islam into a transformative one. This study involved participatory action research, cycling twice through five strategies: imparting knowledge of transformative Islam, cultivating new understandings, developing strategic action plans, implementing these action plans, and reflecting/gathering feedback for further action. This study finds that peasant empowerment can be realized by transforming their religious understandings, and that the five strategies identified above can be employed fruitfully. At the same time, this study provides important feedback to the government and academics, offering a means of sustainably and systematically empowering farmers in Indonesia and around the world, thereby changing their fates and creating justice in agriculture.